Fear of Crime and the Guardian Angels: Attitudes of New York City Subway Riders, 1984 - Kenney, Dennis Jay ([Verlag nicht ermittelbar], 1986)
These data focus on the potential effectiveness of the Guardian Angels in their attempts to combat fear and crime on the New York City subways. Respondents were asked about their perceived fear of crime while riding the subways, the likelihood of their becoming victims of crimes, their opinions about the crime problem on the subways, and their knowledge and observations of the Guardian Angels.